Integration of immigrants in Denmark - Simonsen, Kristina Bakkær (Politica, 2017)
Immigrant integration is a central topic on the agenda, both for politicians and for the wider public. This special issue sheds light on the topic in a Danish context with the ambition of nuancing our understanding of the possibilities and challenges related to integration in different central areas of Danish society. This introduction to the special issue presents the concept of integration, gives an overview of the development of the European academic literature on the topic and discusses the conditions of integration in Denmark and in other European countries.